Acute hypertrophic but not maximal strength loading transiently enhances the kynurenine pathway towards kynurenic acid - Joisten, Niklas; Schumann, Moritz; Schenk, Alexander; Walzik, David; Freitag, Nils; Knoop, Andre; Thevis, Mario; Bloch, Wilhelm; Zimmer, Philipp (Technische Universität Dortmund, 2020)
Purpose Due to distinct immuno- and neuro-modulatory properties, growing research interest focuses on exercise-induced alterations of the kynurenine (KYN) pathway in healthy and clinical populations. To date, knowledge about the impact of different acute strength exercise modalities on the KYN pathway is scarce. Therefore, we investigated the acute effects of hypertrophic (HYP) compared to maximal (MAX) strength loadings on the KYN pathway regulation. Methods Blood samples of twelve healthy males (mean age and weight: 23.5 ± 3.2 years; 77.5 ± 7.5 kg) were collected before (T0), immediately after (T1), and 1 h after completion (T2) of HYP (5 sets with 10 repetitions at 80% of 1RM) and MAX (15 sets with 1RM) loadings performed in a randomized cross-over design. Serum concentrations of tryptophan (TRP), KYN, kynurenic acid (KA), and quinolinic acid (QA) were assessed using high-performance liquid chromatography. Results The KA/KYN ratio increased from T0 to T1 (p = 0.01) and decreased from T1 to T2 (p = 0.011) in HYP, while it was maintained within MAX. Compared to MAX, serum concentrations of KA were greater in HYP at T1 (p = 0.014). Moreover, the QA/KA ratio was significantly lower in HYP than in MAX at T1 (p = 0.002). Conclusion Acute HYP loading led to increases in the metabolic flux yielding KA, thereby possibly promoting immunosuppression and neuroprotection. Our findings emphasize the potential of acute HYP exercise as short-term modulator of KYN pathway downstream to KA in healthy males and need to be proven in other samples.
Eur J Appl Physiol;120
Keywords: Strenuous exercise; Acute exercise; Resistance exercise; Tryptophan metabolism; Kynurenines; Kynurenic acid; 796